Determination of microbiological quality of boiled crayfish (Astacus leptodactylus) samples treated with chitosan - Ceylan, Zafer; Inanli, Ayşe Gürel; Basahel, Abdulrahman; Karaboga, Dervis; Tahsinyilmaz, Mustafa (Sciendo, 2024)
Coating crayfish (Astacus leptodactylus) meat samples with chitosan solution could be an effective approach to limit microbiological spoilage. During the 18-day cold storage period at 2°C±1, mesophilic aerobic bacteria (MABc), psychrophilic bacteria (PBc), yeast mold count (YMc), anaerobic bacteria (AnBc), and Enterobacteriaceae growth in the samples coated with chitosan (0.5% and 1%) and also control group samples were tested. Crayfish samples coated with chitosan (0.5% and 1%) had a lower TMABc (6.58 to 4.60 log CFU/g: up to 30.09%), TPBc (3.77 to 1.99 log CFU/g: up to 47.21%), TYMc (1.84 to 1.27 log CFU/g: up to 30.97%), TAnBc (3.69 to 1.88 log CFU/g: up to 49.05%), and Enterobacteriaceae (3.49 to 2.60 log CFU/g: up to 25.50%) counts as compared with control group samples at 2°C±1. The results particularly based on mesophilic anaerobic bacteria suggested that the application would be a promising approach to limit microbial growth and provide food safety for boiled crayfish meat samples. © 2024 Zafer Ceylan et al., published by Sciendo.
Keywords: biopolymer; cooking; crustacean; food safety; preservation